University Accreditation Application - Genta Sahuri; Habayl Huda (IT for Society, 2018)
Accreditation is very complex and delicate procedure. It has to be done carefully, mistake can lead poor accreditation result. The common mistake is human error. Handling a lot questions, the result will be less accurate. Having wrong accreditation result can give bad result to the university who may actually get good accreditation result. Accreditation application let user to modify input and assessment anytime he wants. If user includes incorrect input, he can edit it by going back to input form and if user misjudged in assessing, he can go back to assessment and fix it. So, before getting accreditation result, user simply can check the assessment point of each aspect. Thus, this feature is necessary in assisting user to complete a particular accreditation project in a more effective manner.